CONCEPT OF INFORMATIZATION AND METHODS FOR COMPUTER SCIENCE TEACHING - Zaytseva, Т.В. (Journal of Information Technologies in Education (ITE), 2018)
According to the informatization concept of education, the course of methods of computer science teaching should not be limited to the study of the subject of computer science, but to ensure the implementation of a whole group of main goals, such as: familiarizing students with new areas of knowledge that are directly or indirectly related to computer science, acquiring competencies in using information technologies, the ability to identify and develop the abilities of students by special methods, the introduction of educational innovative forms into school practice. Being a discipline of the methodical cycle related to information technologies, the methods of computer science teaching leads to the comprehension of the experience of using information technologies by a person and it plays a corrective role in the computerization of education in general. In the current state of education, it is not enough to know the subject’s actual material and specific guidelines for teaching computer science in school, although this knowledge and skills have an important factor in teacher’s training. A modern teacher should have a high level of methodological and general culture, the whole complex of both general scientific and subject competences. General questions of methods of computer science teaching are largely formulated, and techniques of teaching a number of basic topics of the school course have been developed in detail. But the constant process of updating science, the openness of computer science to everything new sets the task - to teach a student how to develop techniques independently, methodical creativity by transferring not only knowledge and skills in the field of informatics techniques, but also developing specific subject competences and student’s creative work experience.